"Dig for Bloody Victory" - Brown, G (2012)
Most people’s perceptions of the Second World War leave little room for static, attritional fighting; instead, free-flowing manoeuvre warfare, such as Blitzkrieg, is seen as the norm. In reality, however, much of the terrain fought over in 1939-45 was unsuitable for such a war and, as a result, bloody attritional battles and trench fighting were common. Thus ordinary infantrymen spent the majority of their time at the front burrowing underground for protection. Although these trenches were never as fixed or elaborate as those on the Western Front a generation earlier, the men who served in Italy, Normandy, Holland and Germany, nonetheless shared an experience remarkably similar to that of their predecessors in Flanders, Picardy, Champagne and Artois. This is an area which has been largely neglected by scholars. While the first war produced a mountain of books on the experience of trench warfare, the same cannot be said of the second war. This thesis will attempt to fill that gap by providing a comprehensive analysis of static warfare in the Second World War from the point of view of British infantry morale. It draws widely on contemporary letters and diaries, psychiatric and medical reports and official documentation – not to mention personal narratives and accounts published after the war – and will attempt to interpret these sources in light of modern research and organise them into a logical framework. Ultimately it is hoped that this will provide fresh insight into a relatively under-researched area of twentieth century history.